Chewing Lice (Mallophaga) Parasitic on Pycnonotus leucotis in Al- Diwaniya city - Hamza, H. M.; Marhoon, I. A.; Nema, H. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
This study done was carried out identify the species of parasitical lice on.   White cheeked bulbul(Pycnonotus leucotis).For this purpose 24 birds were collected from AlDiwaniya city and examined externally for the lice.The results showed that  P. leucotis  was infested with five species of chewing lice with a total infestation ratio of 87.5% .These species were:- Menacanthus sp., Columbicola columbae , Bonomiella columba , Coloceras damicorne and  Alcedoecus sp.       The result of this study represents the first isolation of these species from white cheeked bulbul in Iraq.The species were recorded from P. leucotis as a new host for such parasites. Menacanthus sp. was appeared in a high ratio and intensity of infestation (79.2% and 9.2, respectively), while B.columbae was appeared in a lower ratio and intensity of infestation (12.5% and 0.5,  respectively). The bird's sex showed no any effect that there isnâ€™t  infestation ratio where as a significant difference was found for types of infestation: the ratio of  infestation with  two kinds of chewing lice (61.9 %) was the most prevalent  among types of  infestation .